Analysis of indoor MIMO channel capacity using spatial diversity technique - Abd Aziz, Mohamad Zoinol Abidin; Daud, Zakiah; Suaidi, Mohamad Kadim; A. Rahim, Mohamad Kamal (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
This paper focus on simulation and measurement of MIMO channel capacity for indoor propagation. A spatial diversity method is employed during measurement and simulation process. The investigation on the channel capacity for various distance and spacing of both transmitter and receiver antenna have been done. The investigations of channel capacity are included with difference distance between transmitter and receiver sides and different in element antenna spacing. For the simulation, the path loss for the free space and physical effect are been considered. The 2x2 rectangular microstrip patch array antenna is used in order to characterize channel parameter at 2.4GHz operating frequency. Measurement process for 4x4 antenna configuration is done in UTeM Microwave Laboratory. The capacities of MIMO channel also decrease by increasing the distance between transmit and receive antenna.